Unemployment and entrepreneurship in the Covid-19 pandemic and its effects on Brazilian society - Calça, Katia Gobatti; Maciel, Mitali Daian Alves; Cerqueira-Adão, Sebastião Ailton da Rosa (Revista de Administração da UFSM, 2022)
Purpose - This research aimed to analyze the relationship between unemployment and entrepreneurship in Brazil, from 2016 to 2021, focusing on the COVID-19 pandemic. Design/methodology/approach - Quantitative, descriptive research, using the survey method, through the IBGE, GEM and Entrepreneur Portal databases. The data were arranged through descriptive and inferential statistics. Findings - There was a growth behavior over time, with main emphasis on the pandemic period, with an increase of 14% in unemployment, 23% in initial entrepreneurship, and 94% in active IMEs (Individual Micro-Entrepreneur). However, unemployment and initial entrepreneurship displayed little association, demonstrating that entrepreneurship in Brazil has much more important relationships with other factors. On the other hand, initial entrepreneurship and the amount of active IMEs showcased a strong relation, to the point that, for every 5 new initial entrepreneurs in the Brazilian market, 1 IME is formalized. Limitations - Use of quantitative research solely, disregarding the use of qualitative analyses, which would make it possible to identify factors that actually influence entrepreneurship. Originality/value - The research exposed, as a great discovery, that there is no relation between unemployment and entrepreneurship in the pandemic period in Brazil, unlike previous scientific and professional studies that claim the existence of such link, opening, therefore, a new perspective on the motivations to start a business in the country.